(untitled) (Bulletin of the International Association for Paleodontology, 2024)
Forensic odontology often necessitates the utilization of either visual or clinical methods for identification. Forensic experts may sometimes use established techniques, such as employing dental age estimation through atlases. Nevertheless, when confronted with large-scale incidents, particularly in mass disasters, the conventional methods can prove to be intricate and time-consuming, making forensic identification more challenging. Consequently, this challenge has prompted many experts to explore the integration of automation into their current practices to enhance overall efficiency and accuracy. This literature review discusses the application of artificial intelligence (AI) as a supporting method in dental age estimation. Based on the studied literature, AI in dental age estimation has the advantage of determining the maturity score of a tooth with a variety of populations and characteristics. Keywords: artificial intelligence, dental age estimation, forensic odontology, legal identity